Assessment of non-syndromic orofacial cleft severity and associated environmental factors in Saudi Arabia: A cross-sectional study - Sultan Musaad Alghamdi; Aziza Johar Aljohar; Rana Abdullah Alamoudi; Najla Sulaiman Alrejaye; Fatma Dawood Abdulhameed; Reema Mahdi Alhussain; Latifa Yousef AlGudaibi; Heba Jafar Sabbagh (Saudi Dental Journal, 2024)
Objective: To evaluate the relationship between different environmental risk factors and the severity of cleft lip with/without palate (CL ± P) and cleft palate (CP) in Saudi Arabia. Methods: This was a cross-sectional national study, of government hospitals in 10 cities distributed across major regions of Saudi Arabia, from June 2020 to June 2021. All newborns with CL ± P or CP were clinically examined and evaluated for cleft phenotype severity using the LAHSHAL classification system. Various environmental factors were evaluated by interviewing parents using a validated questionnaire. The severity of CL ± P and CP was evaluated in relation to environmental factors. Results: We recruited 174 patients with non-syndromic orofacial cleft (NSOFC); 122 (70.1 %) had CL ± P and 52 (29.9 %) had CP. After adjusting the odds ratios by ordinal regression for CL ± P and logistic regression analysis for CP, environmental factors that significantly increased the severity of CL ± P were family history of NSOFC, maternal illnesses, and maternal medication use (P = 0.02, adjusted odds ratio [AOR]:2.70; P = 0.002, AOR:3.70; and P = 0.03, AOR:2.14, respectively). Folic acid supplementation in the first trimester significantly reduced the severity of CL ± P and CP (P = 0.001, AOR:0.18 and P = 0.001, AOR:0.012, respectively). Conclusion: The severity of CL ± P was affected by some maternal exposures during the 3-month pre-gestation period. Therefore, our results suggest the possibility of controlling the severity of NSOFC.